Pengaruh Variasi Campuran Bentonit Terhadap Karakteristik Pasir Cetak Untuk Proses Sand Casting - Shieddieque, Apang Djafar; Putra Nugraha, Ismail; Zaenal Muttahar, Mochammad Iqbal; Heryana, Ghany (Rekayasa, 2022)
The casting process is widely used because it has the advantage of being able to make products with small dimensions to very large dimensions, the use of materials is more efficient, the casting products can be directly used. However, in the casting process, the main triggers for the formation of defects are the nature of the mold, low permeability, low molding compressive strength, low sintering point, unsuitable sand grain distribution, so research is needed to obtain the right type of molding sand as a sand mold in metal casting. The only type of additive is bentonite. Bentonite can absorb water and expands between 8-15 times and remains dispersed in water for a certain period of time. This study aims to examine the effect of a mixture of variations of local bentonite and Australian bentonite on the characteristics of the molding sand for the sand casting process. The tests carried out are in the form of size distribution testing, X-Ray Diffraction, water content testing, compressive strength, and permeability measurements. Bentonite was varied into 5 variations of the mixture with a difference of 20% in each mixture. The results of the large size distribution of silica sand grains were 37.6 GFN. The results of XRD testing of local bentonite showed a higher content of calcium compounds and Australian bentonite contained higher sodium compounds. The largest water content test value is 5.825%. The largest compressive strength test value is 2.7 Kgf /cm2.